La recreación como fundamento para la integración entre el personal docente y estudiantes del Colegio Nacional Técnico El Progreso, de la parroquia el progeso, del cantón Pasaje, en el periodo lectivo 2012-2013. - Quezada Piedra, Telmo Vincio (2013)
The work presented then sewed in the development of a tutorial to strengthen the practice of volleyball students in ninth years of Private College Manuel A. González of Basic Education in the subject of Physical Culture.